Peripheral Estates as Arrival Spaces? Conceptualising Research on Arrival Functions of New Immigrant Destinations - Nihad El-Kayed; Matthias Bernt; Ulrike Hamann; Madlen Pilz (Urban Planning, 2020)
In recent years, the question of how urban spaces support the arrival of immigrants has found increased attention among scholars. The emerging discussion uses terms like arrival cities, arrival neighbourhoods, arrival spaces, arrival contexts, or arrival infrastructures to refer to local conditions which support immigrant inclusion. This discussion, however, tends to focus empirically and conceptually on neighbourhoods or cities with long-standing migration histories. Connected to this, arrival spaces are often conceptualised as spaces with strong migrant support networks and economies, as well as with high levels of functional diversity and a high fluctuation of residents. Less focus is placed on the question of if and how destinations that lack these characteristics support the arrival of new immigrants. This contribution focuses on this by discussing existent conceptualisations of arrival spaces and contrasting them with empirical illustrations of peripheral estate neighbourhoods in east German cities that have experienced a substantial population loss since the 1990s, resulting in the partial demolition of housing and infrastructure. Since the refugee migration to Germany starting in 2015, the population dynamic in these neighbourhoods has changed substantially. We contrast these developments with the literature on arrival contexts in order to reflect the strengths and weaknesses of the concept, specifically regarding the conditions in new destinations where migrant networks and economies are still emerging, functional diversity is low, and the role of residential fluctuation is unclear. While this article draws on empirical material, its major objective is to point out the blind spots in the current discussion around arrival spaces. It develops questions and offers a research agenda that introduces a wider and more varied set of neighbourhoods into the evolving research agenda on arrival spaces.
Keywords: 710; arrival spaces; housing; immigrant destinations; immigrant neighbourhoods; peripheral estates; refugee migration